Шлакощелочные бетоны на мелкозернистых заполнителях - Глуховский В. Д. Виктор Дмитриевич; Кривенко П. В. Павел Васильевич; Старчук В. Н. Владимир Никифорович; Пашков И. А. Игорь Александрович (Киев, Вища школа, 1981)
Авт. указаны на обороте тит. л.